James Baldwin as a Preface to Christian Ethics - Yin, Peng (Journal of the Society of Christian Ethics, 2024)
Christian ethics stands to benefit from its critics. I argue that James Baldwin should be placed among Ludwig Feuerbach, David Hume, Karl Marx, and Friedrich Nietzsche as a salutary preface to Christian ethics, especially in his reflections on race and sexuality. Together these figures underscore some characteristic damages of some Christian beliefs. I show Baldwin’s astute treatment of Christianity in four distinctive voices and suggest the recovery of genres, the appreciation for recent achievements and unfinished tasks in the field, the vigilance about ambivalent ethical implications inherent in Christian doctrine (such as eudaimonism and providentialism), and the unsentimental affective preparation as pedagogical gains of including Baldwin in Christian ethics syllabi.